Pattern separation performance is decreased in patients with early multiple sclerosis. Issue 8 (21st June 2017) - Planche, Vincent; Ruet, Aurélie; Charré‐Morin, Julie; Deloire, Mathilde; Brochet, Bruno; Tourdias, Thomas
Abstract: Background: Hippocampal‐dependent memory impairment is frequent and occurs early during the course of multiple sclerosis (MS). While mechanisms responsible for episodic memory dysfunction in patients with MS remain largely unknown, dentate gyrus structure has been suggested as particularly vulnerable at the early stage of the disease. If true, we hypothesized that the pattern separation component of episodic memory (a function known to be critically dependent to dentate gyrus function) would be impaired in patients with early MS (PweMS). Methods: Thirty eight participants (19 PweMS and 19 healthy controls matched on age, gender and education level) were tested with a behavioral pattern separation task and also for information processing speed and visuospatial episodic memory. Results: We report a significant decrease in pattern separation performance in PweMS compared to healthy controls (27.07 vs. 40.01, p = .030 after Holm–Bonferroni correction, d = 1.02) together with a significantly higher pattern completion rate (56.11 vs. 40.95, p = .004 after Holm–Bonferroni correction, d = 1.07) while no difference was found among groups for information processing speed and "global" visuospatial episodic memory regarding learning, long‐term recall or recognition. Conclusion: Our results suggest that behavioral pattern separation task can detect subtle memory decline in patients with MS and argue for early dentate gyrus dysfunction during the course of the disease. Abstract : Pattern separation scores were significantly lower in patients with early MS compared to healthy controls. However, in this sample of subjects, no differences among groups could be found for information processing speed performances and "standard" visuospatial episodic memory tests, suggesting that pattern separation task can detect subtle memory decline in patients with MS. Decreased pattern separation performance argues for an early dentate gyrus dysfunction in MS, in lines with what have been described in the animal models of the disease.